(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Preeclampsia is one of the most severe and complex obstetric disorders and remains a leading cause of maternal and perinatal morbidity and mortality worldwide. Due to its late clinical manifestation, rapid progression, and high risk of severe complications, early identification and prevention of preeclampsia are of paramount importance. In the Surkhandarya region, high birth rates, socio-economic challenges, and limited access to healthcare services in certain areas further increase the risk of preeclampsia-related complications. Therefore, a comprehensive assessment of regional risk factors and the development of effective monitoring strategies are of significant scientific and practical relevance.